2018
DOI: 10.1016/j.isci.2018.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Initial B Cell Activation Induces Metabolic Reprogramming and Mitochondrial Remodeling

Abstract: SummaryB lymphocytes provide adaptive immunity by generating antigen-specific antibodies and supporting the activation of T cells. Little is known about how global metabolism supports naive B cell activation to enable an effective immune response. By coupling RNA sequencing (RNA-seq) data with glucose isotopomer tracing, we show that stimulated B cells increase programs for oxidative phosphorylation (OXPHOS), the tricarboxylic acid (TCA) cycle, and nucleotide biosynthesis, but not glycolysis. Isotopomer tracin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
216
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 227 publications
(259 citation statements)
references
References 25 publications
15
216
2
Order By: Relevance
“…125 In normal B cells, PPP is normally kept low through the action of the transcription factors PAX5 and IKZF1 that specifically repress G6PD and other PPP enzymes. 30 Diffuse large B-cell lymphomas also develop addiction to the mitochondrial protein deacetylase SIRT3 regardless of DLBCL mutation profile or cell-of-origin. 32 This generates NADPH, which provides antioxidant protection to proliferating cells.…”
Section: Dys Reg Ul Ati On Of G C Me Tabolis Mmentioning
confidence: 99%
“…125 In normal B cells, PPP is normally kept low through the action of the transcription factors PAX5 and IKZF1 that specifically repress G6PD and other PPP enzymes. 30 Diffuse large B-cell lymphomas also develop addiction to the mitochondrial protein deacetylase SIRT3 regardless of DLBCL mutation profile or cell-of-origin. 32 This generates NADPH, which provides antioxidant protection to proliferating cells.…”
Section: Dys Reg Ul Ati On Of G C Me Tabolis Mmentioning
confidence: 99%
“…The hypoxic niche of long-term haematopoietic stem cells is consistent with their reliance on glycolysis rather than OXPHOS for energy requirements. 17,24 However, the comparative metabolic landscape of B and T lineages is not yet well understood. 19 Activation of both mature B and T lymphocytes leads to the remodelling of their metabolism, 20 the most striking feature being the upregulation of glycolytic ATP production in both B-and T-cells despite oxygen-replete conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, targeting glycolytic pathways in both in vitro and in vivo studies disrupted antibody production . Further studies have shown that B lymphocytes undergo metabolic adaptation by increasing mitochondrial biogenesis and glucose uptake . A recent study showed that activated B lymphocytes upregulate oxidative phosphorylation (OXPHOS), the tricarboxylic acid cycle (TCA), and nucleotide biosynthesis, but not glycolysis.…”
Section: Metabolism Of Plasma Cells and B Lymphocytesmentioning
confidence: 99%
“…Inhibiting OXPHOS or culturing B lymphocytes with glutamine‐free media causes a reduction in their proliferation and differentiation, suggesting that activated B cells utilize glutamine to fuel the TCA. Although glucose can be directed to the pentose phosphate pathway to generate ribose‐5‐phosphate for DNA and RNA synthesis, it can also be directed toward lipid synthesis via de novo fatty acid synthesis to support the rapid replication of activated B cells . Activation of B lymphocytes by LPS upregulates ATP‐citrate lyase (ACLY) levels and activity, generating cytosolic acetyl‐CoA released from the mitochondria .…”
Section: Metabolism Of Plasma Cells and B Lymphocytesmentioning
confidence: 99%